BLOOD RESULTS IN PIGS INFECTED WITH STREPTOCOCCUS SUIS INTRANASALLY AND INTRAVENOUSLY - Wiliantari, Putri; Besung, I Nengah Kerta; Mahardika, Gusti Ngurah Kade (Buletin Veteriner Udayana, 2022)
Research has been carried out to elucidate clinical, as well as differences in blood profiles in pigs infected with Streptococcus suis isolated from Bali by intravenous and intranasal infection routes. S.suis isolate of PPB5 were inoculated intranasally and intravenously to three pigs respectively. The pigs used in this study were 8 weeks old. In intranasal infection before inoculation, 1% acetic acid was first applied to the nasal cavity, then S. suis inoculum was sprayed (2 x 10 6 ). In intravenous infection, inoculum fluid is injected into the auricular vein. Clinical changes in pigs were observed until day 15. Blood samples were taken before being inoculated with bacteria, 3 rd day after inoculation, and before being euthanized. On the 3 rd day after inoculation, the number of eosinophils was significantly different in the two treatments, while the other blood profiles were not significantly different. All blood indicators in the two treatments were not significantly different before the animals were euthanized on day 15. The increase number of erythrocytes and monocytosis was found in intranasal infections at that day. Hypohaemoglobinemia and decreased PCV are seen in both intranasal and intravenous infections. Further research is needed with a greater number of replications. The S. suis vaccine needs to be developed immediately to reduce the threat to public health and economic losses for farmers.